Modeling of light signaling facilities of airports in simulators of the visual environment of aviation simulators - Кузнецов, С. Л. (Proceedings of National Aviation University (archive), 2002)
The modeling of light signal facilities of airports is considered, simplifications are possible, means of improving the quality of modeling and reducing the cost of modeling due to the consideration of the characteristics of light sources, the environment and the human perception of light.